2022
DOI: 10.1038/s43016-022-00622-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of the sustainability of vertical farming, plant-based alternatives, food delivery services and blockchain in food systems

Abstract: Food system technologies (FSTs) are being developed to accelerate the transformation towards sustainable food systems. Here we conducted a systematic scoping review that accounts for multiple dimensions of sustainability to describe the extent, range and nature of peer-reviewed literature that assesses the sustainability performance of four FSTs: plant-based alternatives, vertical farming, food deliveries and blockchain technology. Included literature had a dominant focus on environmental sustainability and le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Population growth is also creating a competitive environment among agricultural producers, requiring them to innovate to differentiate themselves and compete in the market. In the face of increasing demand and competition, the analysis showed that efficient production requires a shift to sustainable farming, using environmentally friendly methods and green technologies (Bunge et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Population growth is also creating a competitive environment among agricultural producers, requiring them to innovate to differentiate themselves and compete in the market. In the face of increasing demand and competition, the analysis showed that efficient production requires a shift to sustainable farming, using environmentally friendly methods and green technologies (Bunge et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The potential of vertical farming lies in its ability to meet the needs of an expanding global population in a way that is economically feasible, socially just, and environmentally conscious. These benefits will come from technological advancements, increased public acceptance, and a dedication to environmental stewardship (Bunge et al, 2022) [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Vertical farming maximizes the use of vertical space, allowing for the cultivation of crops in stacked layers. Due to its ability to produce more crops per square meter than traditional horizontal farming, this method is appropriate for urban areas with limited land (Bunge et al, 2022;Giurgiu et al, 2015) [10,17] . Vertical farms aim to optimize resource use, including water, nutrients, and energy.…”
Section: Principles Of Vertical Farmingmentioning
confidence: 99%
“…To address potential nutrient deficiencies, individuals should ensure they include a wide variety of nutrient-dense foods in their diets. It has been reported that soy-based cheese analogues exhibit superior nutritional profiles compared to those derived from coconut oil . Therefore, incorporating coconut-based alternatives alongside a varied assortment of fruits, vegetables, whole grains, nuts, seeds, and legumes is recommended to achieve a balanced and nutritionally comprehensive diet. This approach ensures the intake of a broad spectrum of essential nutrients, contributing to overall health and well-being.…”
Section: Challenges and Considerationsmentioning
confidence: 99%